Optimalisasi Keterbukaan Informasi Publik melalui Uji Konsekuensi: Studi Penetapan Informasi yang Dikecualikan di Kabupaten Purworejo - Sapardiyono Sapardiyono; Galih Bagas Soesilo; Agus Budi Santoso (Suara Edukasi Hukum, 2025)
Examines the application of the consequence test as a balancing instrument between openness and confidentiality in determining exempted information within the local government of Purworejo Regency. The study is motivated by the tension between the constitutional right to public information access under Article 28F of the 1945 Constitution and the obligation to protect certain information categorized as exempt under Law No. 14 of 2008. Although the Freedom of Information Act (FOIA) establishes a limited list of exempt information, practices in Purworejo reveal inconsistencies in understanding and implementation, potentially leading to legal consequences such as information disputes at the Information Commission, as well as practical impacts, including low transparency and public participation. Using a normative-empirical legal approach, the research analyzes the legal framework and field implementation, including focus group discussions with stakeholders and a review of the Information Exemption List issued by the PPID (Public Information Disclosure Officer). Findings emphasize the critical need for a strict and proportional application of the consequence test to ensure that information exemptions are based on actual potential harm, not to conceal irregularities. The study recommends strengthening PPID capacity and oversight mechanisms to fully realize good governance principles.